How do the new shipping routes affect Asian liquefied natural gas markets and economy? Case of the Northern Sea Route and Panama Canal expansion. Issue 4 (19th May 2018) - Shibasaki, Ryuichi; Usami, Takashi; Furuichi, Masahiko; Teranishi, Hiroyuki; Kato, Hironori
ABSTRACT: This study focuses on the expected impact of Northern Sea Route (NSR) usage and the Panama Canal (PC) expansion on liquefied natural gas (LNG) imports of Asian countries, from not only the macroeconomic viewpoint but also diversification of the supplying countries. First, the amounts saved from shipping costs due to these events are estimated, based on scenarios on the navigable period of the NSR, transit fee of the NSR considering the exchange rate between the Russian ruble and US dollar, and bunker fuel price. Second, a spatial general equilibrium model based on macroeconomic theory is applied to predict changes in LNG trade patterns and measure economic impacts due to the reduction of shipping costs. Finally, the impacts of NSR usage as well as the PC expansion on LNG imports of Asian countries are discussed based on the calculations. The results show that diversification of supplying countries for LNG imports can be observed, especially in Japan, the largest LNG importer in the world, and other Asian countries are secondarily affected by changes in Japan's import pattern, with limited impacts on these countries' national economies.